La religione atea di Dworkin e la divinizzazione del valore (Stato, Chiese e pluralismo confessionale, 2019)
SOMMARIO: 1. Ateismo religioso e valori - 2. Ateismo moderato, neo-ateismo e ateismo religioso - 3. Alcune considerazioni su indipendenza e inevitabilità dei valori - 4. Conclusioni.Dworkin’s Atheistic Religion and the Divinization of ValueABSTRACT: This essay critically discusses some of the central ideas of Ronald Dworkin’s last book, Religion Without God. In particular, it will be argued that the idea of “religion without God” is not a form of atheism, as Dworkin claims, but a pure religious attitude in which the idea of “theistic entity” of traditional religion is replaced by a new and not less problematic entity, the idea of “value”.